2003
DOI: 10.5194/hess-7-97-2003
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen dynamics in the shallow groundwater of a riparian wetland zone of the Garonne, SW France: nitrate inputs, bacterial densities, organic matter supply and denitrification measurements

Abstract: This study highlights the role of interactions between surface and sub-surface water of the riparian zone of a large river (the Garonne, SW France). Information is given about the role of surface water in supplying Dissolved Organic Carbon (DOC ) to the riparian zone for nitrate removal processes. The densities of bacteria (up to 3.310 6 cell m L -1 ) in groundwater are strongly conditioned by the water moving during flood events. Total bacterial densities in groundwater were related to surface water bacterial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(27 citation statements)
references
References 27 publications
2
25
0
Order By: Relevance
“…Agricultural land use, in combination with factors such as shallow groundwater, high permeability of alluvial deposits and interconnections with surface water, make alluvial aquifers particularly vulnerable to nitrate diffuse pollution (Arauzo et al, 2011). As a result, nitrate concentrations exceeding the limit of 50 mg-NO 3 − L −1 set for groundwater systems in Europe by the Nitrate Directive (91/676/EEC) and the Groundwater Directive (2006/118/EEC) have been reported for several shallow aquifers in floodplain areas (Baillieux et al, 2014;Sánchez-Pérez et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Agricultural land use, in combination with factors such as shallow groundwater, high permeability of alluvial deposits and interconnections with surface water, make alluvial aquifers particularly vulnerable to nitrate diffuse pollution (Arauzo et al, 2011). As a result, nitrate concentrations exceeding the limit of 50 mg-NO 3 − L −1 set for groundwater systems in Europe by the Nitrate Directive (91/676/EEC) and the Groundwater Directive (2006/118/EEC) have been reported for several shallow aquifers in floodplain areas (Baillieux et al, 2014;Sánchez-Pérez et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…In these areas, where surface water rich in organic matter (OM) meets groundwater containing abundant nutrients, denitrification is promoted Sánchez-Pérez et al, 2003). Therefore riparian areas have been shown to be efficient in nitrate pollution mitigation (Vidon and Hill, 2006;Dosskey et al, 2010;Naiman et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our mass balance approach may over-estimate assimilation into biomass by attributing lost N to this pool, but it nevertheless indicates that a large portion of N can be used up by autotrophs and heterotrophs. Although we did not measure bacterial density or microbial community structure in this study, previous studies have shown that the bacterial community is conditioned to respond quickly and efficiently to flooding events (Sánchez-Pérez, 2003). Nitrogen saturation can occur when bacterial communities are overloaded with constantly elevated nitrate concentrations.…”
Section: No − 3 As a Regulator Of Denitrificationmentioning
confidence: 97%
“…This has implications for drinking water utilities in the cost and reliability of treatment to meet the regulation quality. Elevated nitrate concentrations in groundwater may also impact on surface water where baseflow is significant and on groundwater dependent ecosystems (Rozemeijer and Broers, 2007;Sánchez-Pérez et al, 2003). The roles of nitrate and phosphate are interlinked in the surface water eutrophication process (Smolders et al, 2009).…”
Section: Context and Implicationsmentioning
confidence: 99%